Numerical investigation of oleo-pneumatic shock absorber: a multi-fidelity approach - Sheikh Al Shabab, Ahmed; Grenko, Bojan; Vitlaris, Dimitrios; Tsoutsanis, Panagiotis; Antoniadis, Antonis; Skote, Martin (ECCOMAS, 2022)
A representative shock absorber geometry is developed based on the general guidelines available in the literature, and it is validated against experimental measurements from a drop test. Simulations are conducted using a multi-fidelity approach ranging from unsteady scale resolving three-dimensional simulations to dynamic system models. High fidelity simulations provide a detailed insight into the flow physics inside the shock absorber, as well as help calibrate and validate lower fidelity methods, under conditions for which no experimental measurements are available to achieve that purpose. On the other hand, lower fidelity methods are used to efficiently scan the design space and test the dependency of the shock absorber performance on the various design parameters, in addition to identifying parameter combinations that would be of interest to investigate using a high-fidelity approach.
Keywords: shock absorbers; turbulence; multiphase; multifidelity